Efficacy of the educational program “Mi sol” for the prevention of child sexual abuse in children in the city of Juliaca, Peru - Mamani-Benito, Oscar (2020)
This article aimed to determine the effectiveness of the “Mi Sol” program in the prevention of child sexual abuse (ASI, in spanish) through the development of knowledge and prevention skills about it. The study corresponds to a quasi-experimental design, carried out on a group of 28 primary level students from a state educational institution in the city of Juliaca, Perú. Likewise, there was the participation of a control group made up of 20 students. The program called “Mi Sol” developed by UNICEF-Chile was applied, and to test its effectiveness, a questionnaire of knowledge about ASI and prevention skills was applied, which proved to be valid and reliable. The results regarding the variable “Knowledge about ASI” before the intervention showed that the mean score was 22.89 and then 28.32 (p = .009); however, the control group — before the intervention — yielded a result of 22.40 and after 22.45 (p = .241). On the other hand, regarding prevention skills, in the experimental group the mean before the intervention was 19.14 and after 22.14 (p = .024); on the other hand, in the control group it was before 16.95 and after 16.80 (p = .186). It is concluded that the “Mi Sol” program is effective for minors, since it increases knowledge about ASI and develops prevention skills, with the aim of preventing risk situations that come with being a victim of sexual abuse.